PENGARUH DANA BAGI HASIL PAJAK DAN DANA BAGI HASIL SUMBER DAYA ALAM TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN BERAU: PENGARUH DANA BAGI HASIL PAJAK DAN DANA BAGI HASIL SUMBER DAYA ALAM TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN BERAU - IRA I (ECO-BUILD, 2020)
The purpose of this study was to determine the effect of Tax Revenue Sharing Funds and Non Tax Revenue Sharing Funds on the consumption of the Berau Regency, both partially and simultaneously. The usefulness of this research is that the benefits are expected to be able to increase scientific knowledge in economic fields specifically about profit sharing funds. The benefit of this research policy is that it is expected to be a decision making related to revenue sharing funds and furthermore this research is expected to be a reference for future researchers relating to the Tax Revenue Sharing Fund and Non Tax Revenue Sharing Fund. The results of this study are variable Tax Revenue Sharing has a negative and significant effect on regional consumption in the District of Berau. Non-Tax Revenue Sharing Variables have a positive effect on regional consumption in the District of Berau and are not significant on regional consumption consumption in the District of Berau. Non-tax together has no effect on the regional consumption of the district of Berau.